2014
DOI: 10.1038/nrn3745
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of food intake in health and disease

Abstract: Under normal conditions, food intake and energy expenditure are balanced by a homeostatic system that maintains stability of body fat content over time. However, this homeostatic system can be overridden by the activation of ‘emergency response circuits’ that mediate feeding responses to emergent or stressful stimuli. Inhibition of these circuits is therefore permissive for normal energy homeostasis to occur, and their chronic activation can cause profound, even life-threatening, changes in body fat mass. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
560
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 594 publications
(585 citation statements)
references
References 170 publications
(170 reference statements)
12
560
0
13
Order By: Relevance
“…uDM is characterised by hyperphagia, hyperglucagonaemia and hypercorticosteronaemia, and each of these is thought to increase glucose production and promote hyperglycaemia [23]. At the same time, the hypothalamicpituitary-thyroid (HPT) axis is inhibited and, similar to other conditions of leptin deficiency (ob/ob mice and fasting), each of these abnormalities is corrected by leptin treatment [24].…”
Section: Mechanisms Mediating the Glucose-lowering Effects Of Leptinmentioning
confidence: 99%
“…uDM is characterised by hyperphagia, hyperglucagonaemia and hypercorticosteronaemia, and each of these is thought to increase glucose production and promote hyperglycaemia [23]. At the same time, the hypothalamicpituitary-thyroid (HPT) axis is inhibited and, similar to other conditions of leptin deficiency (ob/ob mice and fasting), each of these abnormalities is corrected by leptin treatment [24].…”
Section: Mechanisms Mediating the Glucose-lowering Effects Of Leptinmentioning
confidence: 99%
“…Considering that hunger ratings were comparable between conditions, it may be concluded that intranasal insulin did not affect hunger motivation, but rather acted via satiating factors that contribute to the termination of a meal. We did not find discernible treatment-induced changes in ghrelin and leptin, two hormones of paramount relevance for food intake control (Morton et al, 2014). A mild insulininduced decrease in plasma glucose concentration apparently was restricted to the young participants although our study was not designed to detect respective differences between age groups.…”
Section: Discussionmentioning
confidence: 83%
“…Eating behavior is tightly regulated by central nervous circuitries that receive hormonal feedback on body fat stores and nutritional status from the body periphery (Morton et al, 2014). In addition to the adipocyte-derived hormone leptin, insulin is one of the major peripheral signals that contribute to the central nervous control of ingestive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Il soupçonna une dérégulation hormonale au niveau hypothalamique [38]. L'hypothalamus apparaît comme un centre intégrateur des signaux périphériques contrôlant l'équilibre entre la prise alimentaire et la dépense énergétique [39] (voir Figure 1A). Il possède des neurones ciliés exprimant les protéines BBS, et est ciliopathies font partie d'une classe émergente de maladies géné-tiques rares, qui affectent le bon fonctionnement du cil primaire et pour lesquelles il existe une grande variabilité phénotypique (voir Tableau I) [11].…”
Section: L'hypothèse D'un Dysfonctionnement Hypothalamiqueunclassified